Long Non-coding RNA RUNDC3A-AS1 Promotes Lung Metastasis of Thyroid Cancer via Targeting the miR-182-5p/ADAM9 - Ma, Dawei; Zhu, Yan; Zhang, Xiao; Zhang, Jia; Chen, Wei; Chen, Xinyuan; Qian, Yichun; Zhao, Yanbin; Hu, Tingting; Yao, Zhangyu; Zhao, Wei; Zhang, Yuan; et al. (Frontiers in Cell and Developmental Biology, 2021)
Long non-coding RNAs (lncRNAs) have been identified as influential indicators in variety of malignancies. Among which, LncRNA RUNDC3A-AS1 is reported to upregulate in thyroid cancer. However, the expression pattern and the pathological function of lncRNA RUNDC3A-AS1 in thyroid cancer is unclear. In this study, we examined the expression levels of lncRNA RUNDC3A-AS1 in the thyroid cancer tissues and cell lines via RT-qPCR analysis. The effects of RUNDC3A-AS1 on thyroid cancer cell metastasis were detected by transwell chamber assay, scratch assay in vitro and lung metastasis model in vivo. The results indicated that RUNDC3A-AS1 was highly expressed in the thyroid cancer tissues and cell lines. Functionally, knockdown of RUNDC3A-AS1 could repress the migration and invasion of thyroid cancer cells in vitro, and inhibit thyroid cancer metastasis to lung in vivo. Mechanistically, RUNDC3A-AS1 served as an inhibitor of miR-182-5p in tumor tissues and cell lines. RUNDC3A-AS1 inhibited the expression of miR-182-5p to increase the expression level of ADAM9, thus further aggravating the malignancy of thyroid cancer. Therefore, the RUNDC3A-AS1/miR-182-5p/ADAM9 axis may be a potential therapeutic target for the treatment of thyroid cancer metastasis.